Chinese computational linguistics and natural language processing based on naturally annotated big data : 17th China National Conference, CCL 2018, and 6th International Symposium, NLP-NABD 2018, Changsha, China, October 19-21, 2018, Proceedings /: 17th China National Conference, CCL 2018, and 6th International Symposium, NLP-NABD 2018, Changsha, China, October 19-21, 2018, Proceedings. (2018) - Unknown
No abstract available